MIXING METALS UNDER STRIPPING GALACTIC GASEOUS HALOES: RADIATIVE LOSSES - Dedikov, S. Yu.; Shchekinov, Yu. A.; Vasiliev, E. O. (Одеські астрономічні публікації, 2008)
We present two-dimensional numerical model for mixing of metals in the intergalactic medium under stripping of a galactic gaseous halo both in adiabatic and radiative cases. A particular attention is paid to influence of radiative losses on mixing efficiency. We conclude that the statistical features of metal distribution are quite similar to those in adiabatic case.